2008
DOI: 10.1158/0008-5472.can-07-5840
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Glutathione S-Transferase P1–Related Cisplatin Resistance in Osteosarcoma

Abstract: Cisplatin (cis-diamminedichloroplatinum, CDDP) is one of the most used drugs for osteosarcoma chemotherapy. By using a series of CDDP-resistant variants, which were established from the U-2OS and Saos-2 human osteosarcoma cell lines, we found that CDDP resistance was mainly associated with the increase of both the intracellular level and enzymatic activity of glutathione S-transferase P1 (GSTP1). On the basis of these findings, we evaluated the clinical effect of GSTP1 in a series of 34 high-grade osteosarcoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 25 publications
8
132
0
Order By: Relevance
“…Our study reported an effective role of GSTP1 in clinical outcome of osteosarcoma patients, which was in line with previous studies (Pasello et al, 2008;Yang et al, 2012;Zhang et al, 2012). Our study suggests that genetic variation of ABCB1 and GSTP1 could play a critical role in the effectiveness of treatment and overall cancer survival.…”
Section: Discussionsupporting
confidence: 92%
“…Our study reported an effective role of GSTP1 in clinical outcome of osteosarcoma patients, which was in line with previous studies (Pasello et al, 2008;Yang et al, 2012;Zhang et al, 2012). Our study suggests that genetic variation of ABCB1 and GSTP1 could play a critical role in the effectiveness of treatment and overall cancer survival.…”
Section: Discussionsupporting
confidence: 92%
“…The association between GSTP1, ERCC1 and ERCC2 gene polymorphisms with prognosis of previous studies (Pasello et al, 2008;Pasello et al, 2011;Windsor et al, 2012;Zhang et al, 2012). Zhang et al, in 2012, studies 159 patients with osteosarcoma treated with neoadjuvant chemotherapy and did not find any association of increased risk of death from osteosarcoma among patients with GSTP1 Val/Val genotype .…”
Section: Discussionmentioning
confidence: 81%
“…Zhang et al, in 2012, studies 159 patients with osteosarcoma treated with neoadjuvant chemotherapy and did not find any association of increased risk of death from osteosarcoma among patients with GSTP1 Val/Val genotype . However, another two studies conducted in Italy reported GSTP1 Val/Val was associated with the outcome of osteosarcoma, and GSTP1 could be considered a promising new therapeutic possibility for osteosarcoma patients (Pasello et al, 2008;Pasello et al, 2011). The inconsistencey of these results may be explained by differences in different ethnicities, source of control, sample size and etc.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, among these last compounds, 20 and 24 showed an interesting profile, they being among the most effective GSTP1-1 inhibitors (IC 50 ¼ 0.1 mM for The replacement of the 6-hydroxyhexyl chain of 1 with shorter methyl propanoate (25) or ethylacetamido (26) chains, as well as with moieties characterized by insertion of an amide function (27) or carrying a 4-piperidone portion (28,29), yielded compounds with reduced potency against both GSTP1-1 and GSTM2-2. Both the inhibitory activities were promptly restored when a benzyl/tertbutyl carbamate function was added to the methyl propanoate chain (compare 30 and 31 with 25), or by introduction of the highly hydrophobic cyclohexylmethyl (32) or tert-butyl (33) chain at the C4-sulfur atom, providing in these cases compounds more potent than 1 but sharing similar inhibition profile and SIs.…”
Section: Inhibition Of Gstp1-1 and Gstm2-2mentioning
confidence: 99%
“…We have previously demonstrated that GSTP1-1 contributes to osteosarcoma chemoresistance, and that targeting GSTP1-1 with 1 may represent a new therapeutic strategy for the treatment of this poorly responding tumor [18,25,26]. Thus, we evaluated the cytotoxic effect of the new NBD compounds 2e40 on the human osteosarcoma U-2OS cell line (Table 1).…”
Section: In Vitro Toxicity On Human Osteosarcoma U-2os Cellsmentioning
confidence: 99%